2020
DOI: 10.1063/5.0025944
|View full text |Cite
|
Sign up to set email alerts
|

Intense ionizing irradiation-induced atomic movement toward recrystallization in 4H-SiC

Abstract: An ultrafast thermal spike within a time interval of a few pico-seconds generated by intense ionizing energy deposited using 100 MeV Ag ions is utilized to study the atomistic details of damage recovery in 4H-SiC. Sequential single ion irradiations were performed using 300 keV Ar and 100 MeV Ag in ⟨0001⟩ 4H-SiC to invoke swift heavy ion (SHI) beam induced epitaxial recrystallization in samples with different degrees of pre-damaged conditions. SHI irradiation was carried out at both room temperature and a low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…The extent of recovery is found to depend on the amount of surrounding crystalline regions around the amorphous/disordered regions, as evident from the higher recovery observed at the boundaries of the crystalline-amorphous region as compared to the centre. This is consistent with previous studies where it has been concluded that epitaxial recrystallization requires a sufficient amount of crystalline surroundings that acts as the deciding factor for the extent of observed damage recovery [10,11,29,30]. Annealing at 1273 K for 30 min recovers significant damage, however, the RBS/C yield remains much greater than that of the pristine.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…The extent of recovery is found to depend on the amount of surrounding crystalline regions around the amorphous/disordered regions, as evident from the higher recovery observed at the boundaries of the crystalline-amorphous region as compared to the centre. This is consistent with previous studies where it has been concluded that epitaxial recrystallization requires a sufficient amount of crystalline surroundings that acts as the deciding factor for the extent of observed damage recovery [10,11,29,30]. Annealing at 1273 K for 30 min recovers significant damage, however, the RBS/C yield remains much greater than that of the pristine.…”
Section: Methodssupporting
confidence: 91%
“…Recently, it has been demonstrated that strain relaxation occurs from ionization-induced annealing of 21 MeV Ni ion in predamaged 4H-SiC [9]. Also, we recently verified that the rapid thermal-spike caused by the strong ionizing energy deposited by 100 MeV Ag ions results in structural and chemical damage recovery in 4H-SiC [10]. Besides, the role of swift heavy ion irradiation in the generation of controlled defects has also been studied [11].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The former can be attributed to the metallic Si 0 (Si–Si bonding) while the latter is the characteristic peak for Si–C bonding. [ 33,34 ] The C 1s spectrum is characterized by a single peak at 283.0 eV. This suggests our CVD grown SiC layer is a mixture of Si and SiC which leads to the unique switching performance of the memristor.…”
Section: Resultsmentioning
confidence: 97%